Rainy and Dry Seasons Are Relevant Factors Affecting Chemical and Antioxidant Properties of Meliponini Honey - Flavia C. Lavinas; Brendo A. Gomes; Marcos V. T. Silva; Raissa Lima; Suzana G. Leitão; Mirian R. L. Moura; Rosineide C. Simas; Renata F. Barbosa; Fabricio O. Silva; Carla S. Carneiro; Igor A. Rodrigues (Foods)
Brazilian stingless bee species produce honey with distinct physicochemical and bioactive properties shaped by environmental factors. This study investigated the effects of the rainy and dry seasons on the physicochemical characteristics, chemical fingerprinting, mineral content, and antioxidant capacity of honey from Melipona mondury and Melipona bicolor. The honey samples were analyzed for their phytochemical properties (official methods), total phenolics (Folin–Ciocalteu method), flavonoid content (aluminum complex formation method), antioxidant capacity (FRAP and ABTS assays), and antioxidant activity (erythrocyte model). The mineral content was assessed via TXRF spectroscopy, and chemical fingerprinting was conducted using mass spectrometry. Chemometric tools were used for the samples’ discriminating analyses, including Principal Component Analysis (PCA) and Partial Least Squares–Discriminant Analysis (PLS-DA). Seasonal variations significantly affected the moisture, total soluble solids, and acidity. In turn, the antioxidant capacity was influenced mainly by the bee species. The mineral composition, particularly potassium, phosphorus, and calcium, remained stable. Multivariate analysis identified m/z ions (VIP scores > 2.5), rather than physicochemical or antioxidant capacity parameters, as critical for seasonal discrimination. The antioxidant activity, assessed by oxidative hemolysis prevention, was robust across the seasons, with M. mondury honey (2 mg·mL−1) from the rainy season outperforming ascorbic acid. These findings underscore the impact of the rainy and dry seasons and the potential of secondary metabolite fingerprinting to identify collection periods.